Measuring Professional Skill Development in U.S. Cities Using Internet Search Queries - Counts, Scott; Cranshaw, Justin (International Conference on Web and Social Media (ICWSM), 2019)
Using a sample of 10 million skill development-related queries from a popular internet search engine, drawn from almost 400 U.S. cities and over a 5 year period (2012 - 2016), we characterize the skills people search for across these cities, and relate them to measures of economic output, including GDP and unemployment. Findings show that differences in the amount, type, and specialization of skill development searches distinguish economically thriving cities from those that are struggling, including explaining variance in future GDP growth after accounting for socioeconomic demographics such as income and poverty levels. Overall, internet-based skill development appears to contribute to rich cities getting richer, with initially well-off cities seeing more and more specialized skill-related searching that in turn aligns with future economic growth.